High amyloid‐β deposition related to depressive symptoms in older individuals with normal cognition: a pilot study. (14th January 2016) - Yasuno, Fumihiko; Kazui, Hiroaki; Morita, Naomi; Kajimoto, Katsufumi; Ihara, Masafumi; Taguchi, Akihiko; Yamamoto, Akihide; Matsuoka, Kiwamu; Kosaka, Jun; Kudo, Takashi; Iida, Hidehiro; Kishimoto, Toshifumi; et al.
Abstract : Objective: Previous studies have reported depressive symptoms in the preclinical stages of Alzheimer's disease (AD). The objective of this study was to determine whether depressive symptoms are associated with cortical amyloid burden. In order to do this, we measured cortical amyloid via 11 C‐labeled Pittsburgh Compound B ([ 11 C]PIB) uptake using positron emission tomography (PET) in cognitively normal subjects. Methods: We performed [ 11 C]PIB‐PET in 29 cognitively normal, older participants. Depressive symptoms were assessed using the 15‐item Geriatric Depression Scale (GDS). Aβ deposition was quantified by binding potential (BPND ), and the association between cortical mean BPND values and GDS scores was evaluated. Analysis of parametric BPND images was performed to examine the relationship between regional BPND and GDS scores. Results: We found a positive correlation between depressive symptoms and mean cortical PIB‐BPND in groups of subjects with middle to high PIB‐BPND . There was little change in GDS‐depression score between subjects with low and middle PIB‐BPND levels, while an increase in GDS was shown in the high PIB‐BPND group. The main BPND increase was localized to the precuneus/posterior cingulate cortex (PCu/PCC) in subjects with high PIB‐BPND, and we found a significant positive relationship between PIB‐BPND in this area and depressive symptoms. Conclusions: Emotional dysregulation because of Aβ neuropathology in the PCu/PCC may relate to depressive symptoms. More specifically, we found that older, cognitively normal patients with depressive episodes were more likely to have underlying AD pathology. Thus, depressive symptoms may increase the predictive ability of the identification of future AD cases. Copyright © 2016 John Wiley & Sons, Ltd.